Formation and development of vegerable-growing area in conditions of the increasing demand for production - Hrybova, Diana; Грибова, Діана Вікторівна; Грибова, Диана Викторовна (My University, 2014)
The purpose of the article is development of approaches on formation and development of vegetable-growing branch in conditions of an increasing demand for production.
Keywords: competitiveness; production; vegetable growing; branch; manufacture; efficiency